ANALISIS ALIH KODE DAN CAMPUR KODE DALAM NOVEL LUKA YANG KAU TINGGAL SENJA TADI KARYA SUSAN ARISANTI (KAJIAN SOSIOLINGUISTIK) - Agoes Hendriyanto; Siska Juliani (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to identify and analyze the phenomenon of code switching and code mixing in the novel Luka yang Kau Tinggal Senja Tadi (LYKTST) by Susan Arisanti. The method used is descriptive qualitative with a structural approach. Data were collected through reading, note-taking, and classification techniques on quotes in the novel that contain elements of code switching and code mixing. The results of the study show that the main character, Nawaila, often does external code switching, there are 6 while external code mixing there are 6 data. Code switching and external code mixing are mainly in the form of phrases in English, Arabic, and other foreign languages. The author uses this foreign language spontaneously and contextually as a form of emotional expression and adjustment to certain social situations. The choice of these phrases reflects adaptation to contemporary communication norms and the desire to convey meaning more precisely and elegantly. The urgency of this finding reveals that code switching and code mixing not only function as a means of communication, but also reflect the dynamics of socio-culture and the flexibility of language use in everyday interactions, especially among today's teenagers.